Distribution range extension of the White-cheeked Cotinga Zaratornis stresemanni (Aves: Cotingidae) in southern Peru - Samata, David (2019)
The White-cheeked Cotinga Zaratornis stresemanni (Koepcke, 1954) (Birds: Cotingidae) is an endemic bird of Peru, specialist of Polylepis forests. Is currently threatened by habitat loss and degradation. In this note, we document records to the northwest of Arequipa department, in southern Peru. These records extend in at least 130 km the austral distribution range and correspond to the first documented records of the species for Arequipa department. We suggest that the White-cheeked Cotinga would be resident in the Polylepis forests in northwest Arequipa.